2011
DOI: 10.1590/s1678-77572011000100011
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of RealSeal, its primer and AH Plus implanted in subcutaneous connective tissue of rats

Abstract: ObjectiveThis study tested rat connective tissue response to RealSeal, RealSeal primer or AH Plus after 7, 15, 30, 60 and 90 days of implantation.Material and methodsThirty Wistar rats had subcutaneous sockets created on their back and received four implants each of polyethylene tubes containing one of the materials tested according to the groups: AH (AH Plus Sealer); RS (RealSeal Sealer); RP (RealSeal Primer); CG (control group – empty tube). After histological processing, sections were analyzed to identify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 16 publications
2
18
1
Order By: Relevance
“…However, the process of collagenization showed ascending values at 30 days, a performance similar to that observed for other materials. 15,22 In addition to the inflammatory infiltrate, circulatory alterations (edema) and multinucleated giant cells proved expressively greater with the Meron cement at 7 days, contrary to the respective results observed for the other cements. This was a proportional response of the body to the presence of aluminum and/or iron ions, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] whereby giant cells are released in the tissue to promote phagocytosis, a process by which the ions are surrounded and contained.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…However, the process of collagenization showed ascending values at 30 days, a performance similar to that observed for other materials. 15,22 In addition to the inflammatory infiltrate, circulatory alterations (edema) and multinucleated giant cells proved expressively greater with the Meron cement at 7 days, contrary to the respective results observed for the other cements. This was a proportional response of the body to the presence of aluminum and/or iron ions, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] whereby giant cells are released in the tissue to promote phagocytosis, a process by which the ions are surrounded and contained.…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, the analysis should be performed by means of qualitative and quantified evaluation. [11][12]15 Biocompatibility studies [22][23] have used polyethylene tubes as controls, 22 because they are considered harmless to the epithelial and conjunctive tissue. For this reason, they were used as such in this experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their tissue compatibility is compromised if some of their components act as antigens or haptens which are able to elicit immune responses 1) . Histological studies on subcutaneous [2][3][4][5][6][7][8] and periapical 9) tissue reactions have shown varying degrees of inflammation being elicited by different sealers. To gain more insight on host response to root canal sealers, it is important and necessary to evaluate their inflammatogenic and immunogenic properties.…”
Section: Introductionmentioning
confidence: 99%
“…134 One study revealed that tissue tolerance of Real Seal cannot be attributed to its primer content. 135 …”
Section: Introductionmentioning
confidence: 99%